2021
DOI: 10.1111/are.15438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia stress on digestive enzyme activities, intestinal structure and the expression of tight junction proteins coding genes in juvenile cobia ( Rachycentron canadum )

Abstract: In this study, juvenile cobia fish (Rachycentron canadum) (body weight: 50.44 ± 2.78 g) were used as a study object to investigate the effects of hypoxia stress (dissolved oxygen: 3.15 ± 0.21 mg/L) on the activities of their digestive enzymes, intestinal morphology and relative expression of tight junction proteins coding genes. Under the experimental conditions, the juvenile cobia were given 28 days of hypoxia stress. The results showed that the activities of digestive enzymes in the intestines of the hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that oxidative stress can lead to excessive ROS production, damage to intestinal structure [41], cell apoptosis [42], and impaired function of the intestinal barrier [43]. Intestinal villus morphology and muscle thickness are important indices to measure the function of the intestinal barrier [13]. Previous studies have shown that hypoxia can significantly affect the morphology and thickness of the intestinal muscle layer [12,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that oxidative stress can lead to excessive ROS production, damage to intestinal structure [41], cell apoptosis [42], and impaired function of the intestinal barrier [43]. Intestinal villus morphology and muscle thickness are important indices to measure the function of the intestinal barrier [13]. Previous studies have shown that hypoxia can significantly affect the morphology and thickness of the intestinal muscle layer [12,44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that hypoxic stress significantly affects the intestinal structure of fish. Dong et al found that intermittent hypoxia for 7 days led to the exfoliation of intestinal epithelial cells and a significant decrease in the length of intestinal villi [12]; Yang et al found that the height and width of intestinal villi and the thickness of the muscle layer decreased significantly after 28 days of hypoxic stress [13]. Hypoxia also affects the immune system of fish, and was shown to affect neutrophils and cause inflammation in the intestinal mucosa of Salmo salar [9] and increase oxidative stress and apoptosis-related factors in the intestine of Lateolabrax maculatus [14].…”
Section: Introductionmentioning
confidence: 99%
“…Lipase adopts a colorimetric method, which is defined as the reaction of each gram of tissue protein with the substrate in this reaction system for 1 min at 37°C, and each consumption of 1 mmol of the substrate is an enzyme activity unit. Trypsin adopts the ultraviolet colorimetric method, which is defined as a unit of enzyme activity when the trypsin contained in each milligram of protein changes the absorbance by 0.003 per minute under the reaction of pH 8.0 and 37°C (Yang et al, 2021).…”
Section: Determination Of Digestive and Antioxidant Enzyme Activitiesmentioning
confidence: 99%
“…The tangible obstacle of the enteric canal comprises intestinal epithelial cells in its majority. and tight junctions between cells (Yang et al, 2021). Absorbing cells, goblet cells, and paint cells make up the majority of intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that Bacillus can promote intestinal mucosa development in animals (Ruiz Sella et al, 2021). The intestinal mucosa is essential to enable sh to process and assimilate nutrients and for intestinal microorganisms to adhere to it (Yang et al, 2021). Simultaneously, the muscular layer of the intestinal tract powers peristalsis and promotes the intestinal absorption of nutrients (He et al, 2022).…”
mentioning
confidence: 99%